Determinants of capital expenditure spending in Malaysian palm oil industries: A dynamic panel data analysis - Afza Asyura Mohd Hisham; Zulkefly Abdul Karim; Norlin Khalid (Economic Journal of Emerging Markets, 2019)
This study aims to investigate the determinants of capital expenditure (capex) for Malaysian palm oil companies listed at Bursa Malaysia.  The study uses the dynamic panel data analysis (generalized method of moment) estimation for the sample of 40 palm oil-oriented firms that spanning from year 2000 until 2016. Findings/Originality: The empirical findings revealed that, in the short run and the long run, the capex spending is significantly affected by the cash flow, sale growth, and world crude palm oil price. However, Average Q  significantly influences the capex decision in the long run only. Thus, the policy implication from this study suggests that palm oil-oriented firms should take into account the movement of world crude palm oil (CPO) price in designing their capital expenditure strategy. In addition, proper planning for managing firms’ cash flow and sale growth are also important for expanding their capex in future.